Double wins: Utilizing digital solutions in agriculture to attain gender and climate goals - Singaraju, Niyati; Gakhar, Shalini; Malhotra, Aayushi; Anjana, V; Mittal, Nimisha (Springer, 2025)
Climate change is significantly impacting agrifood systems, with profound effects on women who constitute around 44% of the global agricultural labor force. With limited access to resources, timely and reliable information, and restrictive social norms, women are disproportionately affected by the impacts of climate change. In this chapter, we investigate what role can inclusive digital solutions play in empowering women and making them more resilient to climate risks. By examining high-impact use cases from the Global South, the discussion focuses on how digital tools can empower women by providing access to information, financial resources, and markets, thus overcoming some of those barriers that have historically marginalized them. Key issues addressed include the design and implementation of digital services tailored to women’s needs, enhancing digital literacy, and creating opportunities for capacity building. The chapter emphasizes integrating gender perspectives in digital solutions to create sustainable and resilient agrifood systems. It also outlines the most effective ways to close gender gaps, empowering women to face climate-related challenges and transforming social norms in agriculture. Ultimately, advocating for an urgent and necessary action to include women in digital agrifood transformation and innovations to create a more equitable future.